2020
DOI: 10.1155/2020/1928121
|View full text |Cite
|
Sign up to set email alerts
|

Association of Central Precocious Puberty with a Rare Presentation of Schimmelpenning–Feuerstein–Mims Syndrome in a Peruvian Girl

Abstract: Schimmelpenning–Feuerstein–Mims syndrome (SFM), an epidermal nevus syndrome characterized by skin lesions, has an estimated incidence of 1 per 10 000 live births. Nevus sebaceous, the most common cutaneous lesion, and verrucous nevus, the less frequent lesion, are coupled with a wide range of extracutaneous manifestations. As part of these manifestations, rarely, central precocious puberty can arise. We report the case of a 1-year-5-month-old girl who presented to the Endocrinology and Metabolism Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…Developmental Delays: De Vito et al [60], Israni et al [36], Ullah et al [37]. "Other" includes nystagmus, right-sided weakness, headaches [35], significant scoliosis, and musculoskeletal pains [38]. The patient with scoliosis and musculoskeletal pains was also diagnosed with hypophosphatemia.…”
Section: Graphical Figure 1b: Epidermal Nevus Syndrome (Ens) Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…Developmental Delays: De Vito et al [60], Israni et al [36], Ullah et al [37]. "Other" includes nystagmus, right-sided weakness, headaches [35], significant scoliosis, and musculoskeletal pains [38]. The patient with scoliosis and musculoskeletal pains was also diagnosed with hypophosphatemia.…”
Section: Graphical Figure 1b: Epidermal Nevus Syndrome (Ens) Generalmentioning
confidence: 99%
“…Importantly, the earlier in embryogenesis they occur, the more widespread the nevus and the greater the chance (and more extensive and severe) of extracutaneous anomalies. Among patients diagnosed with NSS (which we consider identical to LNSS), HRAS mutations were the most common, including G13R [34,35,[48][49][50][51], G12C [25], G12S [26], and G13V [23], as were KRAS mutations, specifically G12D [14,22,24,25,26,27,30], G12V [28], G12C [20,53], and A146T [31]. One NRAS mutation (Q61R) was found, marking the first causative NRAS mutation in NSS [5], as well as unique mutations such as in the PRKRIR gene (A1674T, R558S) for one patient, and a mutation in the RRP7A gene (C670T, R224W) in another [27].…”
Section: /6 Mutational Analysismentioning
confidence: 99%
“…6,15 Studies have indicated the presence of androgen receptors in nevus sebaceous, 4 so that lesions take on a verrucous appearance and a more intense color, due to the processes of hyperkeratosis, papillomatosis, and acanthosis. 6,14,15 Finally, the third stage is seen in the adulthood, when there is a higher risk of secondary neoplasm development. 6,15 A linear nevus is usually reported in Schimmelpenning-Feuerstein-Mims syndrome and, as a component of multisystemic disorders, which have been previously described in a wide variety of organs, such as the nervous, ocular, cardiovascular, muscular, urogenital systems, and bones, among others.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…6,15 A linear nevus is usually reported in Schimmelpenning-Feuerstein-Mims syndrome and, as a component of multisystemic disorders, which have been previously described in a wide variety of organs, such as the nervous, ocular, cardiovascular, muscular, urogenital systems, and bones, among others. 14,15,22,23 Aiming to facilitate the identification and clinical diagnosis, Table 1 shows the main disorders that have been previously identified and related to Schimmelpenning-Feuerstein-Mims syndrome, among which the most frequently reported in the literature are: hypophosphatemic rickets, intellectual disability, and cognitive impairment, coloboma and strabismus. 5,11,22…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Conversely, in the rarer individuals with NSS, KRAS appears to be more common in 13 reported individuals in whom the molecular basis has been determined with the identification of postzygotic variants. Of those 13 reported individuals with NSS, KRAS variants account for nine, with HRAS variants in three and NRAS in one ( Groesser et al 2012 ; Sun et al 2013 ; Kuroda et al 2015 ; Igawa et al 2016 ; Jiang et al 2017 ; Mitchell et al 2018 ; Chacon-Camacho et al 2019 ; Nagatsuma et al 2019 ; De los Santos-La Torre et al 2020 ; Pan et al 2020 ; Pepi et al 2021 ). Pathogenic variants tend to be recurrent affecting residues functionally conserved across all RAS proteins ( Groesser et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%